(untitled) (Bulletin KNOB, 2024)
An excavation in Aalsmeer in 2013 revealed the remains of a building with most remarkable foundations, namely blocks of peat. Such blocks, cut from dredged peat and then dried, were widely used as fuel in centuries past. Because peat is sometimes encountered inside buildings, especially in the form of insulation, the question arose as to whether peat was used by builders as an ad hoc, pragmatic solution using a readily available material, or whether it was a more widely used building material in the past. This research question led to a large-scale survey of the literature and archaeological and building history reports. Because peat blocks turn up only sporadically in the course of renovating or demolishing buildings, it is difficult to gauge how widespread its use was. The same applies to the more innovative instances of the use of compressed peat moss. In building archaeological reports and the literature, such discoveries are usually treated as unique occurrences and described anecdotally. However, the survey revealed that the use of peat as a building material is a historical structural phenomenon that, having been rendered obsolete by twentieth-century innovations, was subsequently consigned to oblivion. Mentions of such use in nine teenth-century architecture handbooks and in articles in professional journals from the same period, suggest that the use of peat was far from ad hoc. Interestingly, the use of peat for foundations was specific to certain regions. This was due on the one hand to the ready availability of the material, and on the other to the nature of its properties: its lightness, flexibility and waterproofness made it ideal for building on soft peaty soils. It can be tentatively concluded that this method of construction became popular in the Dutch peatlands from the second quarter of the sixteenth century. One explanation for this is the growing use of hand-held dredges in that period, which greatly increased both production and accessibility. The peat as a building material was used because it was readily available and lightweight, notwithstanding the major drawback of its flammability. This article is an initial attempt to learn more about the use of peat in construction. Systematic survey research is still lacking, so questions regarding the precise extent of below- and above-ground uses, regions, periodization and building types remain as yet unanswered.